2022
DOI: 10.3390/toxics10020070
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Polystyrene Microplastics from Aqueous Solution Using the Metal–Organic Framework Material of ZIF-67

Abstract: Due to the continuous and adverse effects of microplastics on the environment, an increasing number of studies have begun to focus on their migration patterns and removal from aquatic environments. Herein, our study innovatively evaluated the ability of the capacity of ZIF-67, a novel metal–organic framework (MOF) material, to adsorb polystyrene (PS) microplastics (MPs) from aqueous solutions, aiming to explore the potential of MOF materials to remove MPs from wastewater. The adsorption ratio of PSMPs (5 mg/L,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(16 citation statements)
references
References 75 publications
(124 reference statements)
0
16
0
Order By: Relevance
“…Metal–organic frameworks (MOFs) are porous, crystalline materials constructed by the assembly of metal ions and organic ligands, which showed great performance in various applications like gas storage, separation, catalysis, sensing and contaminant removal, etc. Owing to the high porosity, tunable structure, and rich functionality, MOFs show promising properties such as structural and surface tunability as a potential adsorbent for nanoplastics removal from water. Previous research has demonstrated the use of Zr-based-MOFs (UiO-66-OH@MF-3) and Co-based-MOFs (ZIF-67) for the removal of micro-/nanoplastics. However, these MOFs showed limited adsorption capacity (about 34.5 mg/g) toward micro-/nanoplastics. , …”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Metal–organic frameworks (MOFs) are porous, crystalline materials constructed by the assembly of metal ions and organic ligands, which showed great performance in various applications like gas storage, separation, catalysis, sensing and contaminant removal, etc. Owing to the high porosity, tunable structure, and rich functionality, MOFs show promising properties such as structural and surface tunability as a potential adsorbent for nanoplastics removal from water. Previous research has demonstrated the use of Zr-based-MOFs (UiO-66-OH@MF-3) and Co-based-MOFs (ZIF-67) for the removal of micro-/nanoplastics. However, these MOFs showed limited adsorption capacity (about 34.5 mg/g) toward micro-/nanoplastics. , …”
Section: Introductionmentioning
confidence: 96%
“…However, these MOFs showed limited adsorption capacity (about 34.5 mg/g) toward micro-/nanoplastics. 42,43 Hence, we report using Cr-based-MOFs for efficient removal of polystyrene nanoplastics (PSNPs) from water with enhanced adsorption capacity. We report complete isotherm adsorption experiments, including equilibrium study and kinetic study, at different concentrations of PSNPs and varying operating conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent research, ZIF-67 was investigated as a viable adsorbent material for MPs from water media [ 56 ]. PS MPs with particle dimensions falling in the range of 1.0–3.0 µm were used for simulating MPs waste and their interactions with ZIF-67 particles were studied at a 3–10 pH range and at different temperatures (288–308 K).…”
Section: Mofs As Mps/nps Adsorbentsmentioning
confidence: 99%
“… Entry MOF or MOF-based composite MPs/NPs Application Conditions Process efficiency Ref. 1 ZIF-67 PS (1–3 µm) Adsorbent 5 ppb of MPs in water at a 3–12 pH range, 288–308 K Up to 92.1% of removal at 298 K [ 56 ] 2 MIL-101(Cr) PS (65 nm) Adsorbent 5–100 ppm of NPs in MiliQ water at pH 5–10, 25°C Up to 96% of removal at 5 and 70 ppm, pH 5 [ 57 ] 3 UiO-66-X in a melamine porous foam, X = H, NH 2 , OH, Br and NO 2 PVDF 260–322 nm PMMA 325 nm PS 183 nm Adsorbent 0.5–2 ppm of MPs in water/ethanol (3:1) or simulated seawater environments PMMA, 88.2% PS 85.7% PVDF Up to 95.5% of removal [ 58 ] 4 ZIF-8 in a wood aerogel PVDF (60—110 nm) PS (90―140 nm) Adsorbent 0.5 ppm of MPs in water/ethanol (3:1) and seawater environments Up to 91.4% of removal [ 59 ] 5 PSF/MIL-100 (Fe) mixed matrix membrane PVC (134.6 µm) PE (42.5 µm) Adsorbent Different concentrations of MPs/Nps in water at different pHand in presence of MB Up to 99% of removal [ 60 ] 6 UiO-66(Zr) PET chips Catalytic degradation Solvent-free p...…”
Section: Introductionmentioning
confidence: 99%
“…The main driving forces of this adsorption are hydrogen bonds, stacking and electrostatic interactions. These findings represent a step forward in the field of removing micro-plastics with innovative and eco-sustainable materials [ 20 ]. In the experimental report by P. Guidi et al they have described and studied experimentally, the damage that spills of petroleum and derived oils in water can create on the environment and in particular on living organisms.…”
mentioning
confidence: 99%